2015
DOI: 10.1021/ja512567y
|View full text |Cite
|
Sign up to set email alerts
|

Nylon-3 Polymers Active against Drug-Resistant Candida albicans Biofilms

Abstract: Candida albicans is the most common fungal pathogen in humans, and most diseases produced by C. albicans are associated with biofilms. Previously, we developed nylon-3 polymers with potent activity against planktonic C. albicans and excellent C. albicans vs. mammalian cell selectivity. Here, we show that these nylon-3 polymers have strong and selective activity against drug-resistant C. albicans in biofilms, as manifested by inhibition of biofilm formation and by killing of C. albicans in mature biofilms. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 48 publications
1
93
0
Order By: Relevance
“…[65][66][67][68] By varying the specific structures of cationic groups and hydrophobic groups, the antimicrobial activity against particular microbes can be selectively enhanced as well. [69][70][71][72][73][74][75][76][77] It should be noted that the physical chemistry behind the globally amphiphilic antimicrobial cationic polymers needs to be studied furthermore for providing the guidelines for fabrication of antimicrobial materials with tailor-made structures and functions.…”
Section: Antimicrobial Polymers Y Yang Et Almentioning
confidence: 99%
“…[65][66][67][68] By varying the specific structures of cationic groups and hydrophobic groups, the antimicrobial activity against particular microbes can be selectively enhanced as well. [69][70][71][72][73][74][75][76][77] It should be noted that the physical chemistry behind the globally amphiphilic antimicrobial cationic polymers needs to be studied furthermore for providing the guidelines for fabrication of antimicrobial materials with tailor-made structures and functions.…”
Section: Antimicrobial Polymers Y Yang Et Almentioning
confidence: 99%
“…Hedrick and co-workers demonstrated antimicrobial polymeric hydrogels that can disrupt bacterial and fungal biofilms [37]. Gellman and his group showed that nylon-3 polymers can inhibit and disrupt fungal biofilms [38].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Applying these NM subunit homopolymers to biofilms of C. albicans proved their ability to inhibit fungal biofilm growth down to SMIC 80 (concentration to inhibit 80% of biofilm formation) values of 9.4 µg/mL, whilst displaying very little RBC lysis, even at 2000 µg/mL. 65 When NM subunits were supplemented with hydrophobic groups (CP, CH and CO), antifungal activity was diminished, although the more hydrophobic subunits displayed less dramatic decreases in activity relative to CP, attributed to their antifungal effects. Interestingly the DM subunit has some intrinsic antifungal behaviour, but also intrinsic hemolytic effects, whereby upon replacement of the DM unit with hydrophobic groups, HC 10 values increase.…”
Section: Fig (23) β-Lactam Monomers Used In Studymentioning
confidence: 99%